Genetic interaction between F‐box motif encoding YDR131C and retrograde signaling‐related RTG1 regulates the stress response and apoptosis in Saccharomyces cerevisiae. Issue 10 (26th July 2021) - Shoket, Heena; Pandita, Monika; Sharma, Meenu; Kumar, Ravinder; Rakwal, Ayushi; Wazir, Shreya; Verma, Vijeshwar; Salunke, Deepak B.; Bairwa, Narendra K.
Abstract: The retrograde signaling pathway is well conserved from yeast to humans, which regulates cell adaptation during stress conditions and prevents cell death. One of its components, RTG1 encoded Rtg1p in association with Rtg3p communicates between mitochondria, nucleus, and peroxisome during stress for adaptation, by regulation of transcription. The F‐box motif protein encoded by YDR131C constitutes a part of SCF Ydr131c ‐E3 ligase complex, with unknown function; however, it is known that retrograde signaling is modulated by the E3 ligase complex. This study reports epistasis interaction between YDR131C and RTG1, which regulates cell growth, response to genotoxic stress, decreased apoptosis, resistance to petite mutation, and cell wall integrity. The cells of ydr131cΔrtg1Δ genetic background exhibits growth rate improvement however, sensitivity to hydroxyurea, itraconazole antifungal agent and synthetic indoloquinazoline‐based alkaloid (8‐fluorotryptanthrin, RK64), which disrupts the cell wall integrity in Saccharomyces cerevisiae . The epistatic interaction between YDR131C and RTG1 indicates a link between protein degradation and retrograde signaling pathways.